The mediating role of rumination in the relationship between negative cognitive styles and depression among pregnant women in Guangzhou, China - Liang, Min; Chen, Yu; Liu, Yan; Xiong, Ribo (Frontiers in Psychiatry, 2024)
BackgroundsNegative cognitive styles (NCSs) have been identified as risk factor for the onset of depression. However, little empirical evidence is available to support its role in psychological disorders in the perinatal period. Moreover, less is known about the underlying mechanism in the relation between NCSs and depression in pregnant women. The purpose of this study was to examine the mediation effect of rumination on the relationship between NCSs and antenatal depression (AD). Specifically, the mediation effects of two subtypes of rumination were tested.MethodsA cross-sectional study was conducted from February to May 2023 using anonymous online questionnaire among women in their third trimester of pregnancy in the antenatal care clinic of a tertiary hospital. The Edinburgh Postnatal Depression Scale was used to screen antenatal depression. Attributional Style Questionnaire and Ruminative Responses Scale were employed to assess NCSs and rumination respectively. Correlational analysis of the associations between NCSs, rumination, and AD was conducted. Bootstrap mediation analysis and multiple mediation models were applied to investigate whether rumination, and its brooding and reflection components would mediate the relationship between NCSs and AD.ResultsNCSs had a significant positive effect on depression in pregnant women (c=1.45, SE=0.03, p<0.001, 95%CI: 0.92∼1.70). Rumination mediated the relationship between NCSs and depression in pregnant women (point estimate=0.41, 95%CI: 0.13∼0.79, effect size=0.22, K2 = 0.19). Multiple mediation analysis revealed that brooding, instead of reflection, mediated the relationship between NCSs and depression in pregnant women (point estimate=0.41, 95%CI: 0.15∼0.78).ConclusionThis study provided novel evidence for the role of rumination, specifically its brooding subtype, in shaping the link between NCSs and depression in pregnant women, highlighting potentially useful targets for interventions aimed at preventing the onset of AD.